Chronotherapeutic intervention targeting emotion regulation brain circuitry, symptoms, and suicide risk in adolescents and young adults with bipolar disorder: a pilot randomised trial - Jihoon A Kim; Anjali Sankar; Rebecca Marks; Erin Carrubba; Bernadette Lecza; Susan Quatrano; Linda Spencer; R. Todd Constable; Brian Pittman; Eli R Lebowitz; Wendy K Silverman; Holly A Swartz; et al. (BMJ Mental Health)
Background Mood episodes and high suicide risk of bipolar disorder (BD) are thought to derive from amygdala–ventral prefrontal cortex emotion regulation brain circuitry dysfunction and resulting emotion dysregulation, making these potential intervention targets.Objective To assess feasibility, acceptability, and preliminary efficacy in engaging the emotion regulation targets of two Brain Emotion Circuitry-targeted Self-Monitoring and Regulation Therapy (BE-SMART) variations in adolescents and young adults with BD (BDAYA): BE-SMART-ER, which directly targets emotion regulation, and BE-SMART-DR, a social rhythm therapy (SRT)-based chronotherapeutic intervention designed to reduce daily rhythm (DR) irregularities.Methods In a single-blind, parallel, pilot-randomised trial, 60 BDAYA (aged 16–29 years) were randomised to 12 weekly sessions (9 telehealth) of BE-SMART-DR or BE-SMART-ER. Nineteen BE-SMART-DR and 16 BE-SMART-ER participants completed the intervention, with 11 and 13, respectively, having pre-intervention and post-intervention functional MRI data.Findings In addition to demonstrating feasibility, only BE-SMART-DR showed pre-treatment to post-treatment improvements in DR regularity (Cohen’s d=0.55; 95% CI [0.06, 1.03]), associated with reductions in left amygdala responses to emotional face stimuli (pFWE (family-wise error)-SVC (small volume correction)<0.05), difficulties in emotion regulation (d=0.75; 95% CI [0.23, 1.25]) and suicide risk (d=0.65; 95% CI [0.15, 1.14]). Significant correlations were observed among these changes (p<0.05). Both interventions showed high acceptability and improvements in depression and mania symptoms. No intervention-related adverse events were observed.Conclusions Regularising DRs may enhance emotion regulation brain circuitry functioning, emotion regulation, and reduce suicide risk in BDAYA.Clinical implications Chronotherapeutic interventions regularising DRs, such as SRT, should be studied further as potential treatment strategies for BDAYA.Trial registration number NCT03183388.